A soft gripper with variable stiffness inspired by pangolin scales, toothed pneumatic actuator and autonomous controller. (February 2020) - Sun, Tao; Chen, Yuanlong; Han, Tianyu; Jiao, Chenlei; Lian, Binbin; Song, Yimin
Abstract: Aiming at combining compliant covering and rigid lifting to the object grasping, this paper presents the design principle of a variable stiffness soft gripper and carries out its structural design, gripper fabrication and controller development. The proposed soft finger is composed of a variable stiffness layer and a pneumatic driven layer. The variable stiffness layer is inspired by the pangolins whose scales are flexible in daily activities and become tough when being threatened by predators. A toothed pneumatic actuator is designed to supply power with increased stiffness. The three-finger soft gripper is fabricated by 3D printing and molding of super elastic material. The tests for verifying grasping capability and variable stiffness are implemented. Experimental results show that the gripper can grasp a large variety of objects and achieve enhanced stiffness. The stiffness of the gripper is more than twice higher than the pneumatic gripper without variable stiffness structure. Finally, the control system for autonomous grasping is developed. The control block is divided into the actuation layer, information processing layer and user interface layer. According to the grasping process, the feedback signals in the information processing layer are collected by sensors. A safe grasping assessment is added to the control scheme for changing the gripper stiffness autonomously, which differs from the traditional soft gripper controller. The proposed soft gripper has variable stiffness, enhanced pneumatic input, autonomous control system. Therefore, it has great potential to be applied in the unstructured environment for effective, adaptable and safe object grasping.